PENGARUH METODE JARIMAGIC TERHADAP KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR - Najla Fauziyyah Yusuf; Farhan Fazadiningrat; Azkia Marsyida Fakhriyani; Muhammad Rais Fitra Aminullah; Dian Novita Nababan; Ahmad Fu’adin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to find out how the influence and effectiveness of using the jarimagic method affect the ability to count for elementary school students. The subjects in this study were elementary school students in classes I–VI at Umi Najla's tutoring place. This type of research uses a qualitative descriptive analysis method. The focus of this research is on the effect that using the jarimagic method taught in tutoring has on the numeracy skills of elementary school students in their learning process at school. The techniques used for data collection are interviews and documentation. Researchers used analytical techniques with several stages, namely the processes of data collection, data display, and drawing conclusions or verifying results. The results of the study showed that the jarimagic method used was able to have a fairly good effect, especially in improving students' numeracy skills. Before getting to know the jarimagic method, as many as 84.6% of students carried out arithmetic operations using books or notes. Although most of the students take lessons against their parents' wishes, they still feel happy learning this method. In fact, from the research results, it is known that the majority of students feel that the jarimagic method is easy, and 61.5% of students have mastered this method in less than 1 year. The students also found math to be easier after they mastered the jarimagic method.